The resting-brain of obsessive-compulsive disorder - Moreira, Pedro Silva (2019)
Obsessive–compulsive disorder (OCD) is one of the most debilitating psychiatric conditions, having a dramatic impact on patients’ daily living. In this work, we aimed to explore resting-state functional connectivity in OCD patients, using an independent component analysis. Eighty individuals (40 patients and 40 healthy controls) performed a resting state fMRI protocol. OCD patients displayed reduced functional connectivity (FC) in visual and sensorimotor networks. In addition, patients displayed decreased FC between sensory networks and increased FC between default-mode and cerebellar networks.